Monetary Policy and Corporate Liquid Asset Demand - Choi, Woon.; Kim, Yungsan (Washington, D.C. : International Monetary Fund, 2001)
In contrast to conventional money demand literature, this paper proposes that monetary policy affects corporate liquidity demand directly through a separate channel-what we call "the loan commitment channel." Upon persistent monetary policy shocks, firms make substitutions between sources of funds for intertemporal liquidity management, taking advantage of loan commitments and sluggish movements in loan rates. To test this proposition, we estimate corporate liquidity demand, controlling for firm characteristics, using U.S. quarterly panel data. The results indicate that when monetary policy is tightened, S and P 500 firms initially increase their liquid assets before reducing them, whereas non-S and P firms reduce them more quickly.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet